Nose-to-brain delivery of self-assembled curcumin-lactoferrin nanoparticles: Characterization, neuroprotective effect and in vivo pharmacokinetic study - Li, Linghui; Tan, Liwei; Zhang, Qian; Cheng, Yushan; Liu, Yayuan; Li, Rui; Hou, Shuguang (Frontiers in Bioengineering and Biotechnology, 2023)
Curcumin (CUR) is a natural polyphenol extract with significant anti-oxidation and anti-inflammatory effects, suggesting the great potential for neuroprotection. And lactoferrin (LF), a commonly used oral carrier and targeting ligand, has not been reported as a multifunctional nano-carrier for nose-to-brain delivery. This study aims to develop a nose-to-brain delivery system of curcumin-lactoferrin nanoparticles (CUR-LF NPs), and further to evaluate the neuroprotective effects in vitro and the brain accumulation in vivo. Herein, CUR-LF NPs were prepared by desolvation method with a particle size of 84.8 ± 6.5 nm and a ζ-potential of +22.8 ± 4.3 mV. The permeability coefficient of CUR-LF NPs (4.36 ± 0.79 × 10-6 cm/s) was 50 times higher than curcumin (CUR) suspension (0.09 ± 0.04 × 10-6 cm/s) on MDCK monolayers, indicating that the nanoparticles could improve the absorption efficiency of CUR in the nasal cavity. Moreover, CUR-LF NPs showed excellent protection against Aβ25-35-induced nerve damage in PC12 cells. In vivo pharmacokinetic studies showed that the brain-targeting efficiency of CUR-LF NPs via IN administration was 248.1%, and the nose-to-brain direct transport percentage was 59.7%. Collectively, nose-to-brain delivery of CUR-LF NPs is capable of achieving superior brain enrichment and potential neuroprotective effects.